High pressure electroslag remelting – a new technology of steel refining. (4th August 2014) - Stein, G.; Menzel, J.
The paper presents a process for the nitrogen alloying of steels beyond the solubility limit in a pressurised electroslag remelting furnace using Si3 N4 as nitrogen source. With the aid of this process it is possible to attain highest nitrogen percentages in steels. This opens up favourable perspectives for varying nitrogen contents to obtain engineering materials with markedly enhanced properties for advanced applications. The effect of nitrogen alloying beyond the solubility limit on the manufactureability of high–strength austenitic and ferritic steels is discussed. The fundamentals of the pressurised ESR process are present.